Video Led Learning for Agri-Nutrition Education: A Participatory Assessment - Satyapriya , Premlata Singh , V.Sangeetha , V. Lenin , Sudipta Paul ,; S. Barua (Indian Journal of Extension Education, 2017)
Health is a core concept for quality life. Today’s greatest challenge is to provide sufficient and healthy food to all. There is lack of nutrition knowledge and practices that develop healthy habits. To attain good health, nutrition education has been realised as one of the essential means of helping people to improve and maintain their health. Today electronic media has become an effective tool to impart knowledge. Video based material boost the knowledge and motivate people in developing healthy habits. Educating people with video has been proved to be very effective as it combines the senses of seeing, hearing and text together. Studies have revealed that video extension has the advantage of credibility especially among low literate people. Information has great impact when combined with educational tools. The aim of the study was to assess the effectiveness of nutritional videos among farm women. Semi- interviews were conducted among 42 respondents of Lachoda village of Baghpat district to measure the effectiveness of video presentation. The study was carried out by using videos on semi-stiuetined to assess the effectiveness of the method in terms of video content design, logistics and learning out comes. Avideo programme was specially developed for this purpose. The data were analysed by the specially developed effectiveness index, besides descriptive statistics including mean and standard deviation to assess the level of effectiveness of prepared videos. It was found that the video was highly effective in its all parameters. The content and design of the videos were found highly effective with the effectiveness score 86.71 and 82.90, respectively. Learning outcomes of the videos were also high. After watching the videos, the farm women were in the opinion that they can take care of their family nutrition and they will like to explore more videos on this aspect. The results have indicated more positive attitude of the respondents towards the videos. Overall effectiveness score of videos was found 83.70. It was observed that about nutritional videos have the capacity to increase nutritional knowledge among low literate population, especially rural women.